DESIGN OF MONITORING SYSTEM AND NOTIFICATION HOURMETER USING WEB ON CONTAINER CRANE (CC) - Romadoni, Deni; Astutik, Rini Puji; Surya, Yoedo Ageng (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2021)
Container Crane (CC) is heavy equipment that functions to unload or load containers from the dock to the ship and vice versa, this crane has a measuring device, namely an hourmeter which functions to show how long this crane has been running based on the number of hours. from this hourmeter will be used as a reference for the technician team to carry out maintenance or replacement of a spare part. So far, checking the hourmeter is done manually by visiting the crane one by one and looking directly at the analog hourmeter. For this reason, an hourmeter monitoring system is needed to make use of the Internet of Things to make it more effective. In supporting this system, we use a voltage sensor as a detector that the crane is on, the RTC is a type of timer, the ESP32 is a microcontroller that is equipped with a wifi module, MySQL as a database and web to display digital data from the microcontroller. This hourmeter tool can be used as hourmeter monitoring on Container Crane via the web. This system can display data on the microcontroller which can be viewed via the web and provide notification in the form of an email to the user if the value on the hourmeter has reached the specified limit to prevent damage to the crane due to delays in the maintenance process.